THEMATIC ANALYSIS: POSSIBILITIES FOR EVALUATION OF RESEARCH QUALITY (Annual of the Faculty of Philosophy in Skopje, 2016)
Thematic analysis is widely-used qualitative analytic method within psychology, both in primary qualitative and mixed-method research. This paper outlines what thematic analysis is and how it is used in relation to different epistemological and ontological positions and presents the important features of the different types of thematic analysis including the generic ones. It discusses the necessity of reviewing the process in a systematic way and explains the strategies for assuring stronger reliability (dependability) and validity (credibility) of findings generated by this approach. By highlighting the advantages and weaknesses of thematic analysis, the author concludes with suggesting criteria when this approach is the most suitable solution for data analysis. It is concluded that although thematic analysis as one of the most useful methods for qualitative research its use is limited to research questions that do not require narrower focus and fine nuances in the analysis.
Keywords: THEMATIC ANALYSIS; QUALITATIVE RESEARCH; CREDIBILITY